Strategi Service Quality Sebagai Media dalam Menciptakan Kepuasan dan Loyalitas Pelanggan Jasa Pendidikan - Afni Ma'rufah (LP. Ma'arif Janggan Magetan, 2023)
This article discusses the importance of service quality in creating customer satisfaction and loyalty in the education sector. The article highlights the Total Quality Service (TQS) concept, which emphasizes the effectiveness and efficiency of service delivery. The article also discusses the four characteristics of non-profit service institutions, including intangibility, inseparability, variability, and perishability. The article emphasizes the importance of identifying customer needs and understanding their characteristics to provide satisfactory services. The article also discusses the impact of customer satisfaction and loyalty on the sustainability of educational institutions. The research method used in this article is library research, which involves analyzing and synthesizing existing literature on the topic. The article concludes that providing high-quality services is essential to maintain customer satisfaction and loyalty, which in turn contributes to the reputation, competitiveness, and financial stability of educational institutions.